Comparison of scenario based triage education by lecture and role playing on knowledge and practice of nursing students. (November 2018) - Delnavaz, Samira; Hassankhani, Hadi; Roshangar, Fariborz; Dadashzadeh, Abbas; Sarbakhsh, Parvin; Ghafourifard, Mansour; Fathiazar, Eskandar
Abstract: Introduction: Quick and accurate triage of patients in the emergency department is a key factor for successful management of the emergency situations and ensuring the quality of care. Moreover, triage skills education is one of the important aspects of preparedness of nurses for different emergency situations. The objective of this study was to compare the effect of educating emergency severity index (ESI) triage using lecture and role-playing on the knowledge and practice of nursing students. Methods: This experimental study was conducted in the School of Nursing and Midwifery, Tabriz, Iran, in 2016. In this study, 56 nursing students were selected by convenience sampling method and were randomly divided into two groups. Triage scenarios were taught and presented in two ways by using lecture or role-playing method. One month later, the post-test was taken. Data were collected using a questionnaire assessing the knowledge and practice of ESI and were analysed using SPSS (version 21). Results: The mean knowledge and practice scores in both groups improved significantly (p < 0.05). The post-test score showed a significant difference between the two groups, and the mean score was higher in the role-playing group compared with that of the lecture group (p < 0.05). Discussion: The results showed the effectiveness of both educational methods on students' learning. However, the role-playing method was more effective than the lecture method and is recommended for triage education. In addition, according to the importance of triage, developing the theoretical and practical education courses for nursing students is recommended. Highlights: Emergency nurses in Iran have difficulties in doing triage in emergency care. So, training of this groups is in priority. Nurse educators could find an effective method for educating of triage among nursing students in the field of emergency. Role playing method as a practical method could help nurse students to learn the triage in an effective way.